Unconventional co-existence of plasmon and thermoelectric activity in In:ZnO nanowires1. Issue 56 (19th June 2015) - Catellani, Alessandra; Ruini, Alice; Nardelli, Marco Buongiorno; Calzolari, Arrigo
<x xml:space="preserve">Abstract</x> In:ZnO nanowires present the unique property of being simultaneously plasmonic and thermoelectric materials that can be used to realize coupled plasmonic/thermoelectric power generators.